STUDY ON SPECIES DIVERSITY OF BRACHIONUS (ROTIFERA) CONCERN WITH BARAI POND AT BRAHMAPURI, DIST: CHANDRAPUR - MURKUTE V.B; CHAVAN A.W (The Bioscan, 2026)
Throughout the time of an ample faunistic survey of the lentic ecosystem at Brahmapuri. A total of 15 species are recorded from the Barai pond which is 100 years old. The Purpose of present study is to pay attention towards physiological condition of Rotifers for biomonitering the environmental status of aquatic ecosystem. In the Present Study, Taxonomic notes with a key for their identification are appended and their role as an indicator of pollution is discussed.